Sewage treatment of wineries - Mostova, Valeriya; Bublienko, Natalia; Semenova, Olena (My University, 2020)
The characteristics of winemaking sewage are given. The basic methods of their purification are characterized: mechanical, physical and chemical. The advantages of using anaerobic-aerobic technologies are given, which will allow to increase the efficiency of the process by using biogas as an alternative type of fuel.
Keywords: стічні води (виробництво напоїв); очищення стічних вод; wastewater treatment; біогаз; кафедра екології та екоменеджменту